METHOD OF TEACHING FOREIGN LANGUAGES - Yo'lchiyeva Anora Abdusalom qizi; Sh.N. Turgunov (Лучшие интеллектуальные исследования, 2024)
Abstract. In the article foreign language of teaching the most efficient methods and of them study in the process use seeing will be released .